1, 5‐Diketones Synthesis via Three‐Component Cascade Reaction. Issue 14 (13th October 2015) - Xing, Li‐Juan; Lu, Tao; Fu, Wei‐Li; Lou, Mei‐Mei; Chen, Bo; Wang, Zhi‐Shen; Jin, Yang; Li, Dan; Wang, Bin
Abstract: A mild and efficient cascade synthesis of 1, 5‐diketones from readily available N, N ‐dicyclohexylmethylamine, 1, 3‐dicarbonyl compounds, and trifluoromethyl β‐diketones has been developed. This cascade reaction occurs via an oxidation/Mannich reaction/Cope elimination/Michael addition/retro‐Claisen reaction sequence, and provides multiple CC bond formations in one pot. In addition, exquisite chemoselectivity is achieved in the reaction between 1, 3‐dicarbonyl compounds and trifluoromethyl β‐diketones. Abstract :